The Moderating Role of Perceived Reward on Leadership Style and Policy Involvement Effects on Job Performance among Pharmaceutical Managers - Theophilus Ehidiamen Oamen (Business Management Analysis Journal (BMAJ), 2023)
Management and behavioral sciences literature has established a direct link between rewards and employee performance. However, limited research exists on the role of perceived reward on the effects of policy strategy involvement and leadership style on the performance of pharmaceutical managers. Intuitively, perceived rewards may have a potential impact on the behavior and attitudes of pharmaceutical managers toward work, and invariably job performance. Based on the incentive theory of motivation framework, the study explored the causal effect of leadership style, and policy involvement on job performance, and the moderating effect of perceived reward among pharmaceutical managers. Comparative differences in perception between operational and strategic managers were evaluated. A cross-sectional web-based questionnaire survey of a random stratified sample of managers (103 strategic and 138 operational) engaged in pharmaceutical marketing. Structural equation modeling was used to evaluate the developed model. Construct validity and fit measures of the hypothetical model were adequate. Policy strategy involvement and leadership style had a positive and significant influence on job performance. Moderation analysis showed that low perceived reward significantly weakened the impact of policy engagement on performance. Integrating improved managers’ involvement with policy and strategy development with commensurate rewards is an incentive strategy to improve managers’ job performance. The study was restricted to only two major managerial groups. More job-related behavioral constructs are required to improve the generalizability of findings, which is suggested for further research.